ANALYSIS OF MORAL VALUES IN TERE LIYE’S NOVEL “PULANG” - Dielarenza Destelita Wahana Putri; Marudut Bernadtua Simanjuntak (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Literary works are creations of aesthetic values that the author wants to communicate through writing, such as telling a story in the first person or in the third person. The literary novel "Pulang" by a writer named Dervish with the pen name "Tere Liye". This novel is about traveling home, going through battle after battle, embracing all hatred and pain for peace. This study aims to describe religious moral values, social moral values and personal moral values in the novel by Tere Liye. The research method used is descriptive qualitative. Data collection techniques are library techniques, listening and taking notes. The results of this study determine the moral values in the novel by Tere Liye, namely religious moral values, social moral values and personal moral values. In this novel, Bujang never violates Mamak's mandate that he is forbidden to drink, which shows the existence of religious moral values. In addition, the social moral values in this novel are manifested in togetherness, and mutual cooperation, especially in the Tong family. And the moral value of an individual is how Bujang eliminates his inner fear.